Development of a Reagentless Biosensor for Inorganic Phosphate, Applicable over a Wide Concentration Range - Solscheid, Claudia (Biochemistry, 2015)
[Image: see text] A fluorescent reagentless biosensor for inorganic phosphate (P(i)), based on the E. coli PstS phosphate binding protein, was redesigned to allow measurements of higher P(i) concentrations and at low, substoichiometric concentrations of biosensor. This was achieved by weakening P(i) binding of the previous biosensor, and different approaches are described that could enable this change in properties. The readout, providing response to the P(i) concentration, is delivered by tetramethylrhodamine fluorescence. In addition to two cysteine mutations for rhodamine labeling at positions 17 and 197, the final variant had an I76G mutation in the hinge region between the two lobes that make up the protein. Upon P(i) binding, the lobes rotate on this hinge and the mutation on the hinge lowers affinity ∼200-fold, with a dissociation constant now in the tens to hundreds micromolar range, depending on solution conditions. The signal change on P(i) binding was up to 9-fold, depending on pH. The suitability of the biosensor for steady-state ATPase assays was demonstrated with low biosensor usage and its advantage in ability to cope with P(i) contamination.